A compact omnidirectional to directional frequency reconfigurable antenna for wireless sensor network applications. Issue 7 (1st September 2022) - Jose, Melvin Chamakalayil; Sankararajan, Radha; Sreeja, Balakrishnapillai Suseela; Alsath, Mohammed Gulam Nabi; Kumar, Pratap
Abstract: In the proposed research paper, a novel compact, ultra-wideband electronically switchable dual-band omnidirectional to directional radiation pattern microstrip planar printed rectangular monopole antenna (PRMA) has been presented. The proposed antenna system has an optimum size of 0.26 λ 0 × 0.28 λ 0 . A combination of radiators, reflectors, and two symmetrical grounds does place on the same layer of the rectangular microstrip PRMA. The frequency agility and the radiation pattern from omnidirectional to directional are achieved using two SMD PIN diodes (SMP1340-04LF). The directional radiation patterns with 180° phase shifts are achieved at the C-band frequency spectrum. The parametric study of the proposed antenna system was performed for different design parameters, and the antenna characteristics were analyzed. An antenna prototype is fabricated using the printed circuit board etching method by using RMI UV laser etching and cutting tools. The measurements of the proposed antenna are conducted in an anechoic chamber to validate the simulations. There are three states of operations due to two SMD PIN diodes being used in switching circuits. In state-I, the proposed antenna radiates at 6.185 GHz (5.275–6.6 75 GHz) in the Ф = 270° direction with a gain of 2.1 dBi, whereas in state-II, it radiates at 5.715 GHz (5.05–6.8 GHz) in the Ф = 90° direction with a gain of 2.1 dBi. In state-III, the antenna exhibits the X-band frequency with center frequency at 9.93 GHz (8.845–10.49 GHz), and the omnidirectional pattern offers a gain of 4.1 dBi. The features of the proposed antenna are suitable for high-speed wireless sensor network communication in industries such as chemical reactors in oil and gas and pharmaceuticals. It is also well suited for IoT and 5G-sub-6-GHz applications.